2022
DOI: 10.1108/ccsm-12-2021-0233
|View full text |Cite
|
Sign up to set email alerts
|

Doing well by doing good: why is investing in university social responsibility a good business for higher education institutions cross culturally?

Abstract: PurposeThis paper aims to corroborate the importance of university social responsibility (USR) for universities and to establish a rationale for their investment in a strategically implement socially responsible initiatives and programmes and gain returns from such investments. This purpose can be achieved by examining a complex conceptual model connecting USR with many desired student-related outcomes that leverage the university's competitiveness, long sustainability and contribution to the triple bottom lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
7
0
1
Order By: Relevance
“…Finally, the last paper, titled “Doing well by doing good: why is investing in university social responsibility a good business for higher education institutions cross-culturally?” bridges the gap in the CSR literature by establishing a link between the microfoundations of CSR and sustainable business performance. In this study, El-Kassar et al . (2023) found that social responsibility initiatives engaged by the university help increase student satisfaction and alumni loyalty through student-university identification, perceived university image and service quality.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Finally, the last paper, titled “Doing well by doing good: why is investing in university social responsibility a good business for higher education institutions cross-culturally?” bridges the gap in the CSR literature by establishing a link between the microfoundations of CSR and sustainable business performance. In this study, El-Kassar et al . (2023) found that social responsibility initiatives engaged by the university help increase student satisfaction and alumni loyalty through student-university identification, perceived university image and service quality.…”
mentioning
confidence: 67%
“…bridges the gap in the CSR literature by establishing a link between the microfoundations of CSR and sustainable business performance. In this study, El-Kassar et al (2023) found that social responsibility initiatives engaged by the university help increase student satisfaction and alumni loyalty through student-university identification, perceived university image and service quality. They further note that when university social responsibility is incorporated at the center of its strategy, it complements its teaching and research goals, satisfies stakeholders' expectations and increases competitiveness and sustainable performance.…”
mentioning
confidence: 88%
“…These digital tools allow universities to become more global. Based on the previous studies of El-Kassar et al. (2022) and Areiza-Padilla and Galindo-Becerra (2022), for this research it is considered that more studies should be carried out that analyze CET and XEN but from the university context, which determine their relationship with regard to image, satisfaction, loyalty and quality perceived by both national and foreign students.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scarce literature on XEN is based on for-profit products or services, however, it is even more scarce to find literature on XEN applied in the educational sector at the university level. Previous studies El-Kassar et al (2022) show how the universities of the 21st century have been adapting to attract both students and the best researchers, not only nationally, but also internationally. This shows a projection of universities as global brands, and not only as local brands.…”
Section: Limitations and Future Lines Of Researchmentioning
confidence: 99%
“…El-Kassar et al . (2022) further explore how USR relates to the different factors in a study involving two private universities.…”
Section: Cross-cultural Evidencementioning
confidence: 99%